Doctors' understanding of individualisation of drug treatments: a qualitative interview study. Issue 5 (17th May 2013) - Denford, S; Frost, J; Dieppe, P; Britten, N
Abstract : Objective: To explore doctors' understanding of individualisation of drug treatments, and identify the methods used to achieve individualisation. Design: In this exploratory study, we used in-depth qualitative interviews with doctors to gain insight into their understanding of the term 'individualised treatments' and the methods that they use to achieve it. Participants: 16 general practitioners in 6 rural and 10 urban practices, 2 geriatricians and 2 clinical academics were recruited. Setting: Primary and secondary care in South West of England. Results: Understanding of individualisation varied between doctors, and their initial descriptions of individualisation were not always consistent with subsequent examples of the patients they had treated. Understandings of, and methods used to achieve, individualised treatment were frequently discussed in relation to making drug treatment decisions. Few doctors spoke of using strategies to support patients to individualise their own treatments after the consultation. Conclusions: Despite its widespread use, variation in doctors' understanding of the term individualisation highlights the need for it to be defined. Efforts are needed to develop effective methods that would offer a structured approach to support patients to manage their treatments after consultations.